Differential antiproliferative effects of calcitriol on tumor-derived and matrigel-derived andothelial cells - Chung, I.; Wong, N.K.; Flynn, G.; Yu, W.D.; Johnson, C.S.; Trump, D.L. (2006)
The most active metabolite of vitamin D, calcitriol, is growth inhibitory for various tumor types in vitro and in vivo and inhibits the growth of endothelial cells freshly isolated from tumors tumor-derived endothelial cells (TDEC). We compared the effects of calcitriol on Matrigel-derived endothelial cells (MDEC) and TDEC isolated from Matrigel plugs and squamous cell carcinoma tumors, respectively. TDEC and MDEC expressed vitamin D receptor (VDR) and responded to calcitriol by increasing VDR protein expression. Although no mutations were found in VDR from either cell type, Scatchard plot analysis revealed a higher ligand-binding affinity in TDEC (K-d,K- 0.26 nmol/L) than MDEC (K-d, 0.65 nmol/L). The VDR signaling axis in both cells was intact as shown using nuclear translocation and 24-hydroxylase promoter-luciferase reporter assays. However, unlike TDEC, MDEC were resistant to calcitriol-induced growth inhibition. Calcitriol (10 nmol/L) resulted in a 12.3% growth inhibition of MDEC compared with 47% in TDEC. In TDEC, calcitriol resulted in induction of G(0)/G(1) arrest (10.75%) and reduction of S-phase cells (6.8%) with induction of p27 and down-regulation of p21 protein expression. Apoptotic effects, determined by Annexin V staining were also observed in calcitriol-treated TDEC (38.6%). Calcitriol caused reduced expression of p-Erk and p-Akt and an increase of poly(ADP-ribose) polymerase and caspase-3 cleavage in TDEC. By contrast, none of these effects on cell cycle or apoptosis were seen in calcitriol-treated MDEC. These results show that TDEC were more sensitive than MDEC to the antiproliferative effects of calcitriol despite apparently normal VDR content and structure of signaling axis in both cell types.